PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE MELALUI EMPLOYEE JOB SATISFACTION DAN INNOVATION PADA PERUSAHAAN RETAIL DI SURABAYA - Serley Ocsakawati (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to financial performance, leadership style to employee’s job satisfaction, leadership style to innovation, employee’s job satisfaction to innovation , employee’s job satisfaction to financial performace, and innovation to financial performace on retail firms in Surabaya. This study also aimed to examine the indirect and significant affect of leadership style to financial performance through employee’s job satisfaction and innovation in retail firms in Surabaya.      This study used quantitative approach, whereas the data obtained through the distribution of questionnaire to retail firms in Surabaya. The data obtained processed by using smartPLS software. The result showed that there was positive and significant relationship of leadership style to employee’s job satisfaction, leadership style to innovation, leadership style to financial performance, employee’s job satisfaction to innovation, employee’s job satisfaction to financial performance, and negative and significant relationship affect of innovation to financial performance on retail firms in Surabaya. Employee’s job satisfaction and innovation became as the intervening variable to leadership style and financial performance because the direct relationship between leadership style and financial performance gave larger affect than through innovation and employee job satisfaction.